Better horizontal transmission of a US non‐InDel strain compared with a French InDel strain of porcine epidemic diarrhoea virus. Issue 6 (2nd July 2018) - Gallien, Sarah; Andraud, Mathieu; Moro, Angélique; Lediguerher, Gérald; Morin, Nadège; Gauger, Phillip C.; Bigault, Lionel; Paboeuf, Frédéric; Berri, Mustapha; Rose, Nicolas; Grasland, Béatrice
Abstract: From the severe porcine epidemic diarrhoea (PED) epidemics that struck in 2013 in the United States of America and other countries of North and South America, two types of porcine epidemic diarrhoea virus (PEDV) were isolated, namely the InDel and the non‐InDel strains. They are differentiated by insertions/deletions in the S1 nucleotide sequence of the S gene, and differences in virulence were observed from the clinical cases. In 2014, a PED outbreak occurred in a pig farm in France, from which an InDel strain was isolated. This study aimed at comparing, under experimental conditions, the pathogenicity and the direct and indirect transmissions between a non‐InDel strain isolated from a PED‐affected piglet in 2014 in the USA and the French InDel strain. All infected pigs showed clinical signs with the non‐InDel strain although only the inoculated and direct contact pigs showed clinical signs in the InDel strain group. Although viral RNA was detected in air samples with both strains, the indirect contact pigs remained free from infection with the InDel strain in contrast to the non‐InDel group in which airborne transmission occurred in the indirect contact pigs. All infected pigs shed virus in faeces regardless of PEDV strain with 9 of 30 pigs showing intermittent faecal shedding. The transmission rate by direct contact was found to be 2.17‐fold higher than the non‐InDel strain compared with the InDel. In conclusion, the InDel strain was less pathogenic than the non‐InDel strain in our experimental conditions. The transmission route differed between the two strains. Direct contact was the main transmission route for the InDel strain, although the non‐InDel strain was transmitted through direct contact and indirectly through the air.